Financial Report Governance at the Bitung City Class II Sea and Coast Guard Base Office - Jaya, Triane; Tumbel, Goinpeace H.; Bulo, Laurens (Technium Social Sciences Journal, 2025)
The purpose of this study was to determine and analyze the governance of financial report preparation at the Bitung Class II Sea and Coast Guard Base Office and its determinants. This research uses a qualitative method with the focus of the research, namely first, the governance of financial reports analyzed based on indicators of planning, report preparation procedures, and supervision. Second, the determinant factors are analyzed based on indicators of human resources, information systems and special assets. The results showed that the governance of the preparation of financial statements at the Class II Bitung Sea and Coast Guard Base office has not been running properly and still needs improvement and understanding of accounting standards. The things that influence are still the lack of careful planning and lack of discipline in recording transactions, even though there are already clear procedures related to the preparation of reports and supervision has been carried out regularly according to the SOP. It was also found that human resource skills still tend to be lacking. Officers preparing financial reports still need to attend trainings in accounting and financial reporting so that they can improve their competence in managing and preparing financial reports. In addition, there is a need to strengthen technological infrastructure so that it can produce timely, accurate and accountable financial reports.